Kajian Stilistik dalam Novel Dilan: Dia adalah Dilanku Karya Fidi Baiq - Khotimah, Husnul; Zuriyati, Zuriyati; Anwar, Miftahulkhairah (Universitas Muhammadiyah Surabaya, 2025)
This study explores and analyzes the use of figurative language in the novel Dilan: He Was My Dilan in 1990 by Pidi Baiq through a stylistic approach. The main focus lies in identifying the types of tropes employed in the narrative text and examining their function in constructing meaning, character development, and aesthetic value in popular literature. A qualitative approach is applied using a descriptive-analytic method, with textual analysis of relevant quotations containing stylistic devices. The data are categorized into four major groups of figurative language: comparison, contradiction, association, and repetition. The analysis reveals that Pidi Baiq creatively utilizes various figures of speech such as metaphor, personification, hyperbole, irony, synecdoche, epizeuxis, and euphemism in his storytelling to produce a distinctive, emotional, and communicative narrative style. These stylistic elements not only enhance the literary aesthetics but also strengthen the identity of the main character as a poetic and humorous teenager, establishing intimacy with the target readers. The findings affirm that language in popular fiction carries high stylistic potential and is worthy of linguistic-literary investigation to enrich the understanding of language dynamics and meaning-making in contemporary literary works.